Reproduction of Qualified HR in Tula Region as Factor of Regional Development in New Social and Economic Conditions - N. I. Kiseleva; A. D. Zhukovsky; N. V. Uzyumova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article provides analysis of staff provision of the Tula region enterprises, which was conducted by the authors within the frames of sociologic research accomplished in cooperation with the government of the Tula region. On the basis of obtained findings it was shown that the shortage of young and qualified personnel can cause serious risks for the further social and economic development of the region. According to the research, in new fast changing social, political and economic conditions enterprises and organizations in the Tula region are rather optimistic about their prospects concerning HR. In spite of imposed sanctions the level of optimism nearly at all enterprises is high enough. On the one hand, it is a positive factor, on the other hand, it could demonstrate a bit inadequate and hasty assessment on the part of enterprise and organization top management, which requires further analysis, monitoring and control in dynamics. On the turn of 2021-2022 the Tula region did not show a clear trend of workers’ deficit and in current conditions, according to 70% of experts, companies are manned and do not need any changes even in attracting labour migrants from CIS countries to unskilled positions. At the same time small production companies are ready to reduce staff. The shortage of personnel was observed only at education and steel-making organizations. These findings demonstrate both a positive process and new risks, as the absence of vacancies and high competition on the labour market in the Tula region can increase the migration flux among young people to more developed regions, raise demographic burden on the working population and reduce growth and development potential of the region.